2018
DOI: 10.1016/j.jid.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Host Interactions and Impaired Wound Healing in Mice and Humans: Defining a Role for BD14 and NOD2

Abstract: Chronic wounds cause significant patient morbidity and mortality. A key factor in their etiology is microbial infection, yet skin host-microbiota interactions during wound repair remain poorly understood. Microbiome profiles of noninfected human chronic wounds are associated with subsequent healing outcome. Furthermore, poor clinical healing outcome was associated with increased local expression of the pattern recognition receptor NOD2. To investigate NOD2 function in the context of cutaneous healing, we treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…Yet, recent cultureindependent studies have revealed that DFU microbiomes in the absence of infection are dynamic, heterogeneous, and incredibly complex. Wound bacterial signatures strongly link to healing outcome in noninfected DFUs (14), suggesting a hostmicrobe relationship that is more subtle than previously thought. Indeed, it is likely that DFU bacteria directly modify the wound milieu, altering the local microclimate (e.g., pH) and producing metabolites that directly affect cellular healing.…”
Section: How Infection Impairs Wound Healingmentioning
confidence: 89%
“…Yet, recent cultureindependent studies have revealed that DFU microbiomes in the absence of infection are dynamic, heterogeneous, and incredibly complex. Wound bacterial signatures strongly link to healing outcome in noninfected DFUs (14), suggesting a hostmicrobe relationship that is more subtle than previously thought. Indeed, it is likely that DFU bacteria directly modify the wound milieu, altering the local microclimate (e.g., pH) and producing metabolites that directly affect cellular healing.…”
Section: How Infection Impairs Wound Healingmentioning
confidence: 89%
“…HBD2 also is reported to promote wound healing of intestinal cells in vitro (99) and in vivo by stimulating keratinocyte migration and proliferation in rats (100). The physiological significance of these findings are demonstrated in mice with Defb14 deletion, which display delayed wound healing in vivo, with significantly increased wound area, delayed epithelialisation and an altered wound microbiota (97). In addition, there is an observed increase in classically activated macrophages in these wound sites and a trend towards decreased alternatively activated macrophages, together with an increased bacterial load in the skin (97).…”
Section: Wound Healing Resolutionmentioning
confidence: 93%
“…Characterising chronic wounds, β-defensin expression is found to be decreased in diabetic ulcers (96). This is thought to contribute to increased infection and also to a lack of wound healing, through mechanisms such as stimulating the migration of fibroblasts, as well as the proliferation of keratinocytes (97,98). HBD2 also is reported to promote wound healing of intestinal cells in vitro (99) and in vivo by stimulating keratinocyte migration and proliferation in rats (100).…”
Section: Wound Healing Resolutionmentioning
confidence: 99%
“…This finding supports the idea that the process of inflammatory stimulation via bacterial colonization, although beneficial in many situations, may also adversely impact healing outcomes due to the increased abundance of proteases, reactive oxygen species, and other bioactive substances that delay wound healing. Another study supporting this theory found that nucleotide-binding oligomerization domain-containing protein 2 (NOD2), a pattern recognition receptor that recognizes bacterial peptidoglycans and consequently stimulates a host immune response, was found to be upregulated in non-healing murine cutaneous wounds [ 87 ]. At this point, it appears that various skin microbiota have both advantageous and detrimental effects on host cutaneous tissue in both uninjured and injured skin, which may dictate whether these microbes take on the role of skin commensal or skin pathogen.…”
Section: The Microbiome Wound Healing and Inflammation: Mechanistmentioning
confidence: 99%